The scopes of rural tourism and regional development: A case study of the selected areas of Ampara district - Banu, Nuska (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
Rural tourism involves activities in rural areas, where tourists interact with local culture, heritage, lifestyle, and the natural environment. Regional development is enhancing the economic, social, and environmental well-being of a specific area or region. The study examines the benefits and challenges associated with rural tourism, including economic empowerment, cultural preservation, community engagement, and environmental sustainability. Therefore, the study mainly focuses on identifying the scopes of rural tourism in Ampara district, to find out the regional developmental causes for preferences of tourist arrival and to find the association between preferences of tourist arrival and regional development activities. This study utilizes qualitative and quantitative methods, gathering primary data through direct observation, field visits, interviews, and structured questionnaires. Secondary data includes annual reports from the Divisional Secretariat of Ampara District, related articles, and journals and for the analysis, the study employs ArcGIS 10.8 and Google Earth Pro. The findings suggest that Ampara can serve as a model for rural tourism and regional development in Sri Lanka with a committed approach to sustainable tourism practices. The study provides insights and recommendations for policymakers, stakeholders, and local communities to harness the benefits of rural tourism while ensuring its positive impact on visitors and residents.